Numerical study of the bearing capacity for strip and circular footings on non-homogeneous clay - Ouahab, Mohamed-Younes; Mabrouki, Abdelhak; Mellas, Mekki; Benmeddour, Djamel (Journal of Applied Engineering Science & Technology; Vol 3 No 1 (2017), 2017)
The present study investigates the influence of linear increase of cohesion with depth on the bearing capacity of shallow strip and circular footings. The objective of this study is the elastoplastic analysis of the bearing capacity factors and correction factors in order to indicate the modifications that must be made to the bearing capacity of smooth and rough strip footings, to take into account the case of circular footing on non-homogeneous clay. Normal stresses and failure mechanisms below the strip and circular footings are also examined. In addition, some interesting results are presented concerning the interference of two strip footings. The comparison of the numerical results of the present study with those presented in the literature confirms the capability of the adopted approach.